I want to simplify a expression with a even function`Df[x] == Df[-x]`

like:

`FullSimplify[-(1/2) Df[x - x4] J[x] - 1/2 Df[-x + x4] J[x], Assumptions -> {Df[x] == Df[-x]}]`

This code can not give the desired result like `-Df[-x + x4] J[x]`

.

And the strange thing here is that if I replace x4 with x2, it works well.

`FullSimplify[-(1/2) Df[x - x2] J[x] - 1/2 Df[-x + x2] J[x], Assumptions -> {Df[x] == Df[-x]}]`

will give `-Df[-x + x2] J[x]`

.

So any solutions here for x4 or arbitrary symbol?